Faktor-Faktor Yang Mempengaruhi Ibu Menyusui Tidak Memberikan ASI Secara Eksklusif Di Puskesmas Sidomulyo Kecamatan Tampan Pekanbaru - Maswarni maswarni; Wahyu Hildayanti (Sistem Informasi, 2019)
Mother's milk (ASI) is a white liquid produced by breast milk. Coverage of breast milk in Indonesia is still low, including in the city of Pekanbaru, which is 46.81%. Exclusive breastfeeding according to the World Health Organization only provides breast milk without providing food and drinks for babies from birth to 6 months, except drugs and vitamins. But that does not mean after giving exclusive breastfeeding for 6 months after the milk is released, but still given to babies until the baby receives 2 years. To promote ASI assistance from an early age, it is necessary to continue supporting factors needed to obtain assistance, including the necessary roles: maternal age, education, employment, tradition / culture, support of husband / family and health workers. The purpose of this study was to find out the factors needed by nursing mothers not to give exclusive breastfeeding at Sidomulyo Health Center, Tampan District, Pekanbaru. The sampling technique uses accidental sampling with a sample of 32 respondents with infants aged 0-6 months. The instrument used in this study was a questionnaire. The data analysis technique used with univariate analysis consists of frequency distribution. The results showed that the average maternal age of 18-35 years was 21 respondents (65.6%) while the age of 36-40 was 11 respondents (34.4%), the motivation of maternal education was as high as 29 respondents (90.6%) , the influence of maternal work was obtained by working data as many as 12 respondents (37.5%), the influence of knowledge was obtained less than 27 respondents (84.4%), for traditional / cultural interactions obtained there were 26 respondents (81.2%), for Husband / family support was obtained by supporting 25 respondents (78.1%) and for support from health workers, there was support for 24 respondents (75%). Keywords: mother, exclusive mother's milk, Factors Affecting Mother Income in Exclusive Breastfeeding